Prenatal diagnosis of genetic disorders. Issue 10 (October 2018) - Johnson, Katie; Eason, Jacqueline
Abstract: Genetic disease can occur due to imbalance of whole chromosomes, smaller chromosome microdeletions or duplications, or at the single-gene level where even a single base change can cause significant disease. This review focuses on the methods available to achieve genetic diagnosis of a fetus in pregnancy, both in the context of a family history of a known disease-causing mutation and where there is clinical suspicion of a genetic disorder based on ultrasound findings. Until recently, genetic testing of a fetus invariably required invasive procedures to sample fetal tissue, with associated risk of miscarriage. However, non-invasive methods of achieving prenatal diagnosis by sampling fetal DNA present in maternal blood have undergone considerable development. Current applications and future utility of these techniques are discussed.